The Integralistic State Idea: Reconstruction of Administrative Efforts Perspective - Fradhana Putra Disantara; Ratna Maya Permatasari A. B; Fawaidil Ilmiah; Ruetaitip Chansrakaeo (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
Administrative efforts as part of the state administrative and legal process must be taken as an initial means before the settlement is carried out in court. In this case, administrative efforts are efforts to optimize non-litigation dispute resolution steps. This study attempts to present a prescription for administrative efforts associated with the idea of an integralistic state. This research is legal research. This study uses primary legal materials, including the 1945 Constitution of the Republic of Indonesia, Law No. 30 of 2014 on Government Administration, and Supreme Court Regulation No. 6 of 2018. Secondary legal materials include books, articles, and other scientific works, especially those related to the idea of an integralist state initiated by Supomo. Non-legal materials include legal dictionaries. The approach in this study uses a statutory approach and a conceptual approach. The results of the study confirm that the mandatory administrative effort in the Law No. 30 of 2014 on Government Administration is a progressive step because it emphasizes the values of the civilized nation, which focuses more on non-litigation dispute resolution. In addition, the reconstruction of the practice of administrative efforts needs to be carried out by socializing and providing an understanding of the importance of administrative efforts as well as the need for technical guidelines for the implementation of administrative efforts in each institution as well as increase the capacity of institutional leaders.